Sun protection habits and behaviors of a group of outdoor workers and students from the agricultural and construction sectors in north-Italy - Modenese, Alberto; Loney, Tom; Ruggieri, Francesco Pio; Tornese, Lorenzo; Gobba, Fabriziomaria (La Medicina del Lavoro, 2020)
Background: Despite the relevant frequency of ultraviolet induced adverse health effects in workers, solar ultraviolet radiation (UVR) exposure is an occupational risk not adequately minimized in Italy. Objective: To assess the characteristics and prevalence of sun exposure habits and behaviors in a group of students and outdoor workers (OW) from the agricultural and construction sectors of a north-Italian region. Methods: Based on a previously developed standardized questionnaire, we collected full information on individual sun exposure habits at work and during leisure activities. Results: In 2018, 380 high school students and OW from the agricultural and construction sectors participated in a sun-safety campaign. More than a third (39.0%) of OW reported never using sunglasses, 52.8% never applied sunscreens at work, and a quarter never wear a UV protective hat. Considering leisure-time, students reported more frequent sunburns compared to OW: 25.0% vs. 13.8%; half (51.6%) of students and a third (36.4%) of OW reported never wearing a UV protective hat. A third (30.1%) of students and 37.2% of OW never or only seldom applied sunscreens on holidays. Discussion: The majority of OW in our study reported poor protective solar exposure habits. Young students of the construction and agricultural sectors indicated even worse sun-protective behaviors, both during apprenticeship and leisure activities. Our study highlights the low health literacy related to solar UVR in OW and apprentices. Further educational initiatives are required in Italy to improve the adoption of protective behaviors during outdoor activities.